1989
DOI: 10.1002/jso.2930420307
|View full text |Cite
|
Sign up to set email alerts
|

Free jejunal graft for repair of cervical esophagus

Abstract: We have operated upon six patients with cervical esophageal carcinoma and reconstructed these with free jejunal graft. The pathology of all six patients was squamous cell carcinoma, and no patient had apparent distant metastasis. The procedure was a two team approach. While the surgical oncology team resected the esophageal tumor, the microvascular team harvested the jejunal graft. The range of warm ischemia for the free jejunal graft was 1-2.5 hr, and no graft was lost because of recirculation failure. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
5
1
1
Order By: Relevance
“…Triboulet and colleagues9 reported a higher complication rate after free jejunal interposition compared with gastric pull‐up (47 versus 33 per cent; P < 0·05). The graft failure rate (23·9 per cent) was high in the present series compared with that in other published studies (0–22 per cent)10, 18, 19, 21, 25, 26, associated in most cases with microvascular anastomoses. As in the present study, the venous anastomosis is the most common cause of graft failure18, a problem that might be reduced by using large vessels, such as the internal jugular vein, for anastomosis18, 19.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Triboulet and colleagues9 reported a higher complication rate after free jejunal interposition compared with gastric pull‐up (47 versus 33 per cent; P < 0·05). The graft failure rate (23·9 per cent) was high in the present series compared with that in other published studies (0–22 per cent)10, 18, 19, 21, 25, 26, associated in most cases with microvascular anastomoses. As in the present study, the venous anastomosis is the most common cause of graft failure18, a problem that might be reduced by using large vessels, such as the internal jugular vein, for anastomosis18, 19.…”
Section: Discussioncontrasting
confidence: 59%
“…Apart from feasibility studies with small numbers of patients21, 25, there have been no previous reports in the literature of treating cervical SCC of the oesophagus (excluding hypopharygeal carcinoma) by limited resection of the oesophagus and reconstruction with a free jejunal graft. The present analysis of 109 patients showed a high complication rate of 74·3 per cent, necessitating reoperation in 29·4 per cent of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when morbidity and mortality occurrence is compared, jejunum is superior than colon or stomach for the replacement in adult patients undergoing circular cancer resections 7 and better than other techniques involving muscular or muscle-skin grafts. [6][7][8]10 Once microvascular anastomosis skill is achieved, this procedure seems to be less traumatic and less complicated than alternative procedures for replacement. 6 Large adult series report up to 90.5% of graft success.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, a study has reported severe mucosal damage of JFF implanted in the neck to replace the cervical esophagus at reperfusion after warm ischemia. 16 Among strategies aiming at reducing IRI, cold graft perfusion and preservation is commonly used in intestinal transplantation. 17 We have adopted a similar preservation method for JFF autotransplantation in the neck, which includes a phase of cold ischemia and subsequent reperfusion.…”
Section: Introductionmentioning
confidence: 99%